Caracterização fisiológica e agronômica de híbridos de canola resistentes a herbicidas trizinas ou imidazolinonas - Durigon, Miria Rosa (2016)
The aim of this study was to characterize, under physiological and agronomic aspects, canolahybrids resistant to triazines or imidazolinones herbicides. The experiments were conducted in the city of Passo Fundo, RS, in laboratory, greenhouse and field, using the hybrids Hyola 555TT(triazines resistant), Hyola 571CL (imidazolinones resistant), and Hyola 61 (conventional, without resistance to herbicides). It was evaluated the functionality of acetolactate synthase ALS) enzime; adaptability of hybrids; competitive ability with turnip (Raphanus sativus); effects of application of herbicides inhibitors of photosystem II and of ALS enzime in resistant plants, under visual, physiological and productive aspects; photochemical and biochemical steps of photosynthesis in triazine resistant plants, depending on application or not of the herbicide; photosynthetic potential, vegetative growth and grain yield in field conditions. There is no change in funcionality of the ALS enzime, as a result of genetic mutation that causes imidazolinones resistance, in hybrid Hyola 571CL. Occurs higher photoassimilates allocation to the stem in hybrid Hyola 571CL and, to the leaves, in hybrid Hyola 61. The hybrid Hyola 555TT has lower initial growth than the others. The ability to compete with turnip is similar among the three hybrids, with damage to crop and benefit to weed, when in competition. Triazines and imidazolinones herbicides do not reduce the production of shoot dry matter in resistant canola plants. The application of atrazine does not inhibit permanently the gases exchange in resistant plants, but temporarily reduces the eletron transport rate between the photosystems, and increases the chlorophyll content, increasing the net assimilation rate at eight days after application. Although there are differences between hybrids for the photosynthetic potential and vegetative growth, they do not differ in grain yield.